The impact of different occlusal guard materials on Candida albicans proliferation in the oral cavity: Guard materials effects on candida proliferation in the oral cavity - Hussein Habib, Shukriya; Hanna Martani, Nabeel Seryoka; Rasheed Mohammed, Jawhar (Cellular and Molecular Biology, 2024)
Candida albicans is an opportunistic fungal pathogen. It's a dimorphic fungus with hyphal form that can penetrate and proliferate the oral mucosa. Occlusal guard materials come into direct contact with the oral mucosa and saliva when worn for extended periods, the occlusal guard acts as a reservoir for C. albicans that imposes adverse oral or systemic effects, particularly in medically compromised patients. A randomized controlled trial was conducted among forty volunteers with a history of bruxism. The volunteers were divided into four groups, with each group assigned to wear occlusal guards made of one of the following materials: (Polyethylene Terephthalate-Glycol, Polymethyl methacrylate resin, Ethyl phenylphosphinate 3D printing resin and Chrome-Cobalt Alloy). The study samples were collected after one month, with an additional three months spent assessing C. albicans. A descriptive statistical analysis was performed and compared between groups with different time intervals. The statistical analysis revealed that C. albicans proliferation increased after three months of wearing the occlusal guards, however, the results showed non-significant differences (P = 0.914). Furthermore, the comparative analysis demonstrated that the highest proliferation of C. albicans was found with Polymethyl methacrylate and the least with Chrome-Cobalt Alloy. Within the limitations of this study, it was concluded that reducing wearing time will reduce pathogenic infection by C. albicans, and the occlusal guard with the chrome-cobalt alloy material was better than the other materials in this aspect.